Enhancing Inclusion, Equity, and Access: An Analysis of Higher Education Policies in Nepal - Rawal, Devendra (Far Western Review, 2024)
Higher education is the backbone for the human resource development which are crucial for the economic and socio-cultural development of any country. Unlike other sector, higher education is imperative not only for the welfare of the human beings but also fundamental for nation building through innovation in areas that concern the society. The aim of this paper is to critically analyze the policy arrangements of higher education in Nepal and its impact on enhancing inclusion, equity and access. Adopting Critical Discourse Analysis (CDA) research method which is combined with policy review, it is found that though commendable efforts by the government and the commission have been continuing, the issues of access, equity, and inclusion remain still lacking in some areas. Therefore, more policy and programmatic actions are necessary for improvement the situation. If the policy recommendations outlined above are seriously considered by the Government of Nepal, the commission, universities, and other relevant bodies, it is possible to further promote and improve the state of access, equity, and inclusion in Nepal’s higher education.